ANALYSIS OF THE EFFICIENCY OF BUILDING A NETWORK OF TRANSPORT AND LOGISTICS COMPLEXES BASED ON THE FACTOR-RATING MODEL (Transport systems and technologies, 2022)
The article presents the results of the analysis of the effectiveness of the factor-rating method of solving the problem of finding the optimal location of elements of the logistics transport and customs infrastructure of Ukraine with the minimization of transport work on cargo transportation. A sufficient and economically justified number of logistics transport and customs complexes for processing the imported cargo flow of a given volume has been determined.The study uses methods of systematic and factor analysis of the calculated parameters of cargo processing, taking into account transport, economic and administrative factors of territorial development. It is established that the known methods developed to determine the location of individual transport and logistics centers do not allow to optimize the relevant logistics infrastructure focused on the processing of freight traffic in the transport system of the country.To build an effective solution to the problem of optimal location of several logistics transport and customs complexes, a method for determining the factor-rating potential of urban efficiency for their location in Ukraine, taking into account transport, economic and administrative factors. An assessment of transport work was conducted for 165 settlements of Ukraine, which include cities with a population of more than 30,000 people, as well as settlements with established customs posts or cargo checkpoints across the customs border of Ukraine. For each city, the relative consumption of imported foodstuffs is taken into account.According to the above algorithm, calculations were performed for options that provide for the operation of one to ten logistics transport and customs complexes throughout Ukraine. The analysis of the results of the calculations shows that the volume of transport work is effectively reduced in the case of the creation of 1 to 5 transport and customs logistics complexes. Further increase in the number of logistics transport and customs complexes, and consequently capital investments, does not lead to a significant reduction in total transport work. Accordingly, the factor-rating potential for cities in the zone where the creation of logistics transport and customs complexes is the most rational and has the following values: Dnipro - 0.46; Kyiv - 0.46; Lviv - 0.54; Odesa - 0.69; Kharkiv - 0.62.The results of the evaluation of the effectiveness of the optimal location of logistics transport and customs complexes can be implemented in the Ukrainian transport system in the construction of logistics infrastructure for the processing of cargo flows of sufficiently large volumes.
Keywords: transport and logistics infrastructure, transport and customs complexes, factor-rating method, logistics.